Some Comments on the Social Status of the Uzbek Family in the End of the XIX Century - The First Half of the XX Century - Pardaev, Ahrorqul Hasanovich (International Journal of Psychosocial Rehabilitation, 2020)
The history of the Uzbek family and the system of relations between family members were formed and developed in the course of a long historical development. Its distinctive ethnic features date back to long periods of the past. From this point of view, the Uzbeks, as in all nations of the world, consider the family as the traditional primary link in society, that is, the primary social association of society. This article analyzes the social situation of the Uzbek family in the late XIX - first half of the XX century, its role in the life of the state and society, the role of Uzbek families in the radical socio-economic changes in Turkistan. However, it considers the function of family members, the composition and form of the family as a result of changes in attitudes towards property and its distribution. The country studies the role of Uzbek families in family life, agriculture and animal husbandry, trade relations and economic life, their functions in the creation of material products in social production. The article also analyzes the historical development of the family during this period, the economy, the traditional and modern way of life, and reveals the lifestyle and economic relations of the Uzbek family.